The Value of Cervical Smears Collected with The ThinPrep Technique in The Detection of Endometrial Cancer - Batukan, Cem; Özgün, Tuncay; Türkyılmaz, Çağdaş; Özçelik, Bülent; Soyuer, Işın; Serin, Serdar (Gynecology Obstetrics & Reproductive Medicine, 2007)
OBJECTIVE: As liquid-based cervical cytology show promise for detecting endometrial adenocarcinoma, the aim of this study was to evaluate the cytological findings in liquid-based cytology of women in with endometrial cancer. Pap smear findings were correlated with histological grade and stage of the tumor to determine whether the presence of atypical cells have any prognostic value. STUDY DESIGN: This prospective study comprises 51 women with endometrial cancer from which a pre-operative cervical Thinprep Pap smear was available. In all cases endometrial thickness was measured transvaginally. The Bethesda nomenclature system for cervico-vaginal cytology was used to define atypical glandular cells (AGCs), atypical squamous cells (ASCs) and endometrial adenocarcinoma cells (EACs). Statistical analysis was done with the independent T test and χ2 test. RESULTS: Cytological atypia was present in a total 26 (51%) cases. AGCs or EACs were present in Pap smears of 19 (37%) women. The rate of FIGO grade 2-3 tumor in patients with and without AGCs/EACs was 36.8% (7/19) and 12.5% (4/32), respectively (p=0.09). Figures for endometrial thickness were 14.8 ± 5.6mm and 16.8 ± 6.6mm, respectively (p=0.3). Thirty-two percent (6/19) of patients with AGCs/EACs were FIGO stage 1C or more, whereas the rate for patients with normal cytology was 20% (5/25) (p=0.59). CONCLUSION: The sensitivity of the ThinPrep Pap smear in detecting endometrial cancer is low. AGCs/EACs on Pap smear do not correlate with tumor grade or stage and there is no association between endometrial thickness and incidence of AGCs/EACs on Pap smear.